Generative Linguistics and Its Impact on Linguistic Studies in Morocco - Al-Adel, Mustafa (El Omda in Linguistics and Discourse Analysis, 2019)
<section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:32c27e8d-0406-4310-8c57-7cfb6e3aa634-28" data-testid="conversation-turn-58" data-scroll-anchor="true" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="9e8d4210-32f4-4933-b268-0138362e73af" data-message-model-slug="gpt-5-mini" data-turn-start-message="true"> Modern linguistics underwent a significant shift with the emergence of Transformational Generative Linguistics by the American linguist Noam Chomsky, who built his new theory on mental-syntactic foundations and, through his linguistic models, provided precise analyses of many language issues. Transformational Generative Linguistics subsequently made its way into linguistic studies in the Arab cultural context, thanks to the considerable openness of Arab linguists to developments in linguistics outside the Arab world. Initially, the teaching approach was led by a group of researchers aiming to introduce American linguistics to the Arab reader. It later found a clearer path through the work of Abdelkader Al-Fassi Al-Fihri, who played a significant role in bringing Transformational Generative (Semantic) Linguistics closer to the Arab audience, thanks to his linguistic efforts and valuable proposals addressing many issues of the Arabic language. Among the main objectives of this paper is to shed light on this linguistic trend, as well as to highlight the key features of Transformational Generative Linguistics in Morocco.